Chemical fingerprints of large organic molecules in scanning tunneling microscopy: Imaging adsorbate-substrate coupling of metalloporphyrins - Buchner, Florian; Warnick, Karl-Georg; Wölfle, Thorsten; Görling, Andreas; Steinrück, Hans-Peter; Hieringer, Wolfgang; Marbach, Hubertus (Journal of Physical Chemistry C, 2009)
In this combined experimental and theoretical work we demonstrate at the example of tetraphenylporphyrins on Ag(111) how differences in individual adsorbate orbitals and their interaction with the substrate can be exploited to switch the appearance of the adsorbate in scanning tunneling microscopy (STM) experiments, such that electronically and chemically very similar large molecules become distinguishable in STM. In particular, an intermixed layer consisting of 2HTPP (TPP ) tetraphenylporphyrin), CoTPP, and FeTPP molecules on Ag(111) was investigated, and it is demonstrated that STM images acquired with different bias voltages constitute fingerprints of the different molecules within the intermixed layer. By means of density functional calculations the observed features could be explained in detail and traced back to a direct orbital interaction of the adsorbed molecule with the surface. The explicit consideration of the surface in the calculations therefore turned out to be decisive to achieve good agreement with experiment. © 2009 American Chemical Society.

Conformational flexibility of metalloporphyrins studied by density-functional calculations - Wölfle, Thorsten; Hieringer, Wolfgang; Görling, Andreas (Physical Chemistry Chemical Physics, 2008)
Reliable energetic data on the conformational flexibility of organic molecules are important ingredients to better understand the adsorption of such molecules on solid surfaces. Herein, the conformational flexibility of the phenyl substituents in metallo tetraphenyl porphyrins (M-TPP, M = Zn, Co) and metallo tert-butyl tetraphenyl porphyrins (M-TTBPP, M = Zn, Co) has been studied in detail for the first time using density-functional methods. For each molecule, a relaxed two-dimensional potential energy surface scan has been calculated for the two angles describing the rotation and the out-of-plane bending of the phenyl substituents. The results quantify that the molecules are rather flexible close to the energetic minimum while more extreme twisting or tilting of the phenyl substituents results in high-energy deformations of the porphyrin core from planarity due to steric repulsions of adjacent hydrogen atoms. © the Owner Societies.

High Resolution Scanning Tunneling Microscopy of a 1D Coordination Polymer with Imidazole-Based N,N,O Ligands on HOPG - Fischer, Nina V.; Mitra, Utpal; Warnick, Karl-Georg; Dremov, Viatcheslav; Stocker, Michael; Wölfle, Thorsten; Hieringer, Wolfgang; Heinemann, Frank Wilhelm; Burzlaff, Nicolai; Görling, Andreas; Müller, Paul (Chemistry - A European Journal, 2014)
Novel k(3)-N,N,O ligands tend to form 1D coordination polymer strands. Deposition of 1D structures on highly oriented pyrolytic graphite (HOPG) was achieved from diluted solutions and polymer strands have been studied on HOPG by AFM/STM. Single strands were mapped by STM and their electronic properties were subsequently characterized by current imaging tunneling spectroscopy (CITS). Periodic density functional calculations simulating a polymer strand deposited on a HOPG surface are in agreement with the zig-zag structure indicated by experimental findings. Both the observed periodicity and the Zn-Zn distances can be reproduced in the simulations. Van der Waals interactions were found to play a major role for the geometry of the isolated polymer strand, for the adsorption geometry on HOPG, as well as for the adsorption energy.
Keywords: atomic force microscopy; coordination polymers; ligand design; scanning tunneling microscopy; zinc

Synthesis and photoinduced electron-transfer properties of phthalocyanine-[60]fullerene conjugates. - Quintiliani, M.; Kahnt, Axel; Wölfle, Thorsten; Hieringer, Wolfgang; Vázquez, P.; Görling, Andreas; Guldi, Dirk Michael; Torres, T. (Chemistry - A European Journal, 2008)
A series of three novel ZnPc-C conjugates (Pc = phthalocyanine) 1a-c bearing different spacers (single, double, and triple bond) between the two electroactive moieties was synthesized and compared to that of ZnPc-C conjugate 2, in which the two electroactive moieties are linked directly. The synthetic strategy - towards the preparation of 1a-c - involved palladium-catalyzed cross-coupling reactions over a monoiodophthalocyanine precursor 4 to introduce the corresponding spacer, and subsequent dipolar cycloaddition reaction to C . Detailed photophysical investigations of 1a-c and 2 prompted an intramolecular electron transfer that evolves from the photoexcited ZnPc to the electron-accepting C . In particular, with the help of femtosecond laser photolysis charge separation was indeed confirmed as the major deactivation channel. Complementary time-dependent density functional calculations supported the spectral assignment, namely, the spectral identity of the ZnPc radical cation and the C radical anion as seen in the differential absorption spectra. The lifetimes of the correspondingly formed radical ion-pair states depend markedly on the solvent polarity: they increase as polarity decreases. Similarly, although to a lesser extent, the nature of the linker impacts the lifetime of the radical ion-pair states. In general, the lifetimes of these states tend to be shortest in the system that lacks any spacer at all (2), whereas the longest lifetimes were found in the system that carries the triple-bond spacer (1a). © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.